Comparative Efficacy of Functional Endoscopic Sinus Surgery and Conventional Polypectomy in Treating Nasal Polyps - Naveed Ahmed, Muhammad Iqbal Musakhail, Mehmood Ullah, Mohammad Afzal, Ikram Ullah, Wajih Ud Din Shinwari (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Nasal polyps are non-cancerous growths in the nasal or sinus lining that significantly affect a patient’s quality of life, particularly in chronic rhinosinusitis (CRS). Surgical intervention becomes necessary when conservative treatments fail. The study aims to evaluate the efficacy of Functional Endoscopic Sinus Surgery (FESS) in comparison with conventional polypectomy for treating nasal polyps. Objective: To compare the outcomes of FESS with conventional polypectomy in terms of symptom improvement, recurrence rates, postoperative complications, and quality of life in patients with nasal polyps. Methods: A total of 70 patients with nasal polyps were randomly assigned to undergo either FESS or conventional polypectomy. Various preoperative and postoperative outcomes, including symptom severity, polyp recurrence, complications, and quality of life, were measured using validated tools. Results: Both FESS and conventional polypectomy resulted in significant symptom improvement. However, FESS showed better outcomes with lower recurrence rates and fewer postoperative complications compared to conventional polypectomy. Quality of life was significantly better in the FESS group postoperatively. Conclusion: FESS offers superior outcomes in terms of symptom relief, reduced recurrence rates, and fewer complications compared to conventional polypectomy in the treatment of nasal polyps. Keywords: Nasal polyps, Functional Endoscopic Sinus Surgery, Conventional polypectomy, Chronic rhinosinusitis, Polyp recurrence, Postoperative complications, Quality of life